2015
DOI: 10.1002/hyp.10461
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic characteristics of rill flow on steep slopes

Abstract: Abstract:Rill erosion is a dominant sediment source on sloping lands. However, the amount of soil loss from rills on steep slopes is vastly more than that on gentle slopes because of differences in rill shape and hydraulic patterns. The aims of this paper are to determine the hydrodynamic characteristics of rills and the friction coefficients in steep slope conditions and to propose modifications of some hydraulic parameters used in soil loss prediction models. A series of inflow experiments was conducted on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 28 publications
4
65
1
Order By: Relevance
“…Under the condition of rainfall intensities kept the same, the Froude numbers increased with higher slope gradients, and this relationship became more obvious on steeper slopes. Our results are different with other findings (Guo et al, 2013;Peng et al, 2015;Zhang et al, 2002) which both Re and Fr are greater than our values. The cause of those differences may be explained by the effective input water rate (greater rainfall intensities and slope gradients) and soil type.…”
Section: Results and Discussion Flow Hydraulic Characteristicscontrasting
confidence: 99%
See 2 more Smart Citations
“…Under the condition of rainfall intensities kept the same, the Froude numbers increased with higher slope gradients, and this relationship became more obvious on steeper slopes. Our results are different with other findings (Guo et al, 2013;Peng et al, 2015;Zhang et al, 2002) which both Re and Fr are greater than our values. The cause of those differences may be explained by the effective input water rate (greater rainfall intensities and slope gradients) and soil type.…”
Section: Results and Discussion Flow Hydraulic Characteristicscontrasting
confidence: 99%
“…The Darcy-Weisbach friction coefficients did not show a definitive relationship with Reynolds numbers. Our results agree with other findings (Nearing et al, 1997;Peng et al, 2015;Zhang et al, 2014) which indicated that the Reynolds number was not a good predictor of hydraulic roughness on hillslope. Furthermore, the date from our experiments indicated that the Darcy-Weisbach friction coefficients are primarily influenced by slope gradient.…”
Section: Results and Discussion Flow Hydraulic Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…13). However, in the following stage, there was no obvious variation trend that could be determined as the flow discharge increased, while flow vellocity usually increased with increasing flow discharge in slope erosion (Jiang et al, 2018;Peng, Zhang, & Zhang, 2015). However, in the following stage, there was no obvious variation trend that could be determined as the flow discharge increased, while flow vellocity usually increased with increasing flow discharge in slope erosion (Jiang et al, 2018;Peng, Zhang, & Zhang, 2015).…”
Section: Sediment Dischargementioning
confidence: 94%
“…Peng et al, 2015;Di Stefano et al, 2018). The first step to a better description of hydraulics in rills is to carry out a comprehensive characterization of rill bed geometry under various conditions and to identify the (role of the) controlling factors.…”
Section: Introductionmentioning
confidence: 99%